Explorer 1, anniversario americano e scientifico - Bernardini, Fabrizio (GEOmedia, 2008)
Explorer 1: a science and american anniversary In reaction to the public and political turmoil originated by the Soviet launch of the first two satellites, Sputnik 1 and 2, the US Government tried to detach academically from the issue, pursuing the development of the Vanguard project. The failure of the first Vanguard launch, in front of TV cameras from all over the world, prompted the Administration to accept the "hacked” solution proposed by Wernher Von Braun and his team. Very quickly the Jupiter-C rocket, derived from existing hardware, and a new satellite, Explorer 1, where readied and launched with success: United States had their first orbiting satellite. Science, however, had a a greater gain - the achievement of a second place in the space race.